PERENCANAAN STRUKTUR BANGUNAN BAWAH ABUTMENT JEMBATAN DESA SEKERAT KECAMATAN BENGALON KABUPATEN KUTAI TIMUR - ROHADI, SLAMET (KURVA S JURNAL MAHASISWA, 2017)
The bridge is a part of a highway that is functioning to connect a brokenroad due to obstacles such as rivers, lakes, valleys, ravines and others. In theplanning and work of the bridge Under the Structure Planning can not be ignored.Part of this bridge structure located at the bottom is crucial for the strength andsecurity of buildings on it. And for direct link between upper bridge structure withunder bridge structure is "Abutment" which is also included in under bridgestructure. Abutment of a building that functions to continue the load (live load anddead load) from the upper building to the foundation and the foundation passes tothe ground. The loading rules used to plan the bridge refer to Indonesian NationalStandard (SNI) T-02-2005, T-03-2005,In the design of this thesis the discussions covered include the structureunder the bridge building between the abutment and foundation. The plannedfoundation is a pile foundation. The building structure under a sliver village bridgeis planned to receive loads and forces from the upper structure with a span lengthof 30 meters and a 9 meter wide bridge. Based on the calculation of the structureunder the bridge abutment, obtained abutment dimensions: width 3.8 m, length 11m and height 5.2 m. With its own abutment weight of 2211.38 kN, the foundationfor the Sekerat Village bridge uses a 60 cm diameter pile foundation.